The Psychometric Properties and Typology of the Chinese Version of the Emotional Style Scale for Gifted Students in Middle School - Min-Ying Tsai (SAGE Open)
The study aimed to verify the psychometric properties of the emotional-style scale and explore different clusters of emotional styles. An emotional style scale was completed in three districts of western Taiwan using stratified random sampling. The study confirmed the reliability and convergent validity of each subscale in a sample of 712 academically gifted students. An emotional style scale for gifted junior high school students was validated with a 25-item self-reported measure. A bi-factor structure model proved the best theoretical factor structure for emotional style. In addition, three clusters of emotional styles were identified in the study. Researchers and educators could use the emotional-style scale in the future to identify and address the emotional needs of gifted junior high school students.